Twee kerstliederen [Bladmuziek]. - Broeckx, Jan; De Mont, Pol; Lambrechts, Lambrecht (Antwerpen : Phalesius, 1925)
Deze brochure bevat volgende liederen
Te Bethlehem
Kerstvisioen
Partituren voor : zang en klavier
Nederlands
Partituur
Keywords: partituren; liederen